2005
DOI: 10.1152/ajplung.00227.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of constitutive neutrophil apoptosis by the α,β-unsaturated aldehydes acrolein and 4-hydroxynonenal

Abstract: Reactive alpha,beta-unsaturated aldehydes are major components of common environmental pollutants and are products of lipid oxidation. Although these aldehydes have been demonstrated to induce apoptotic cell death in various cell types, we recently observed that the alpha,beta-unsaturated aldehyde acrolein (ACR) can inhibit constitutive apoptosis of polymorphonuclear neutrophils and thus potentially contribute to chronic inflammation. The present study was designed to investigate the biochemical mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 59 publications
7
54
0
Order By: Relevance
“…We used Annexin V, an anticoagulant protein with high affinity and selectivity for phosphatidylserine (PS), to detect PS exteriorization, and propidium iodide (PI), a membrane impermeable dye, to monitor cell membrane integrity. Consistent with previous reports (8)(9)(10)(11), CSE and nicotine significantly reduced neutrophil spontaneous death. The most significant effects were observed at 36 h and 54 h (Fig.…”
Section: Cse and Nicotine Block Akt Deactivation And Delay Neutrophilsupporting
confidence: 93%
See 1 more Smart Citation
“…We used Annexin V, an anticoagulant protein with high affinity and selectivity for phosphatidylserine (PS), to detect PS exteriorization, and propidium iodide (PI), a membrane impermeable dye, to monitor cell membrane integrity. Consistent with previous reports (8)(9)(10)(11), CSE and nicotine significantly reduced neutrophil spontaneous death. The most significant effects were observed at 36 h and 54 h (Fig.…”
Section: Cse and Nicotine Block Akt Deactivation And Delay Neutrophilsupporting
confidence: 93%
“…Some of the chemical constituents of cigarette smoke (CS), such as nicotine and acrolein, have been shown to directly delay neutrophil spontaneous death (9)(10)(11), providing a mechanism for the massive accumulation of neutrophils in the lungs of smoke-induced COPD patients. Here, we investigate the mechanism by which CS reduces neutrophil spontaneous death.…”
mentioning
confidence: 99%
“…Cysteines also are uniquely targeted by alkylating species (such as cyclopentenone prostaglandins, acrolein), hydroxynonenal and avicins (which can be formed endogenously, or encountered through environmental insults [41,42]), and by acylation (which has important roles in localizing proteins to the membranes [43]). While a protein can have many cysteine residues, few are reactive (typically those in the thiolate, S − form).…”
Section: Oxidizable Amino Acids: Reactive Cysteines As Redox Targetsmentioning
confidence: 99%
“…A recent study demonstrated that caspase-3 activation during TNFα-induced apoptosis was negatively regulated by Sglutathionylation, and could be reversed through the thiol transferase activity of Grx [135]. Not suprisingly, caspase activation can also be negatively regulated by direct cysteine alkylation with biologically generated electrophiles, such as acrolein or hydroxynonenal [42,136].…”
Section: Regulation Of Proteasesmentioning
confidence: 99%
“…Both acrolein and ROS can deplete cellular glutathione. This is the mechanism by which acrolein inhibits neutrophil caspase activation and apoptosis (15,16). Cigarette smoke depletes glutathione by irreversibly reacting with glutathione derivatives and binding them to acrolein (17).…”
mentioning
confidence: 99%